RAFT synthesis of thioether-based, AB diblock copolymer nanocarriers for reactive oxygen species–triggered release. (June 2021) - Quek, J.Y.; Dabare, P.R.L.; Bright, R.; Postma, A.; Vasilev, K.
Abstract: A well-defined AB diblock copolymer of 2-vinyl-4, 4-dimethylazlactone (VDA) and N, N -dimethylacrylamide (DMA) was generated by reversible addition-fragmentation chain transfer (RAFT) radical polymerization. The VDA-DMA diblock copolymer was reacted with 2-(methylthio)ethylamine (MTEA) and 3-(methylthio)propylamine (MTPA) to yield two novel thioether functional diblock copolymers whose structure was confirmed using 1 H NMR and FTIR spectroscopy. Both diblock copolymers formed micelles (20–30 nm) in aqueous media as confirmed by dynamic light scattering (DLS) and transmission electron microscopy. The self-assembled micelles were loaded with Nile Red, a model hydrophobic drug to study their ROS-triggered release mechanism. On addition of hydrogen peroxide (H2 O2 ), the most common ROS species, the hydrophobic thioether core of these micelles oxidized, and both diblock copolymers became more hydrophilic. This triggered their disassembly and subsequent cargo release as characterized by UV–visible spectroscopy. The Nile Red loaded micelles demonstrated similar in-vitro ROS-mediated release when exposed to endogenous oxidants in a model inflammation environment simulated by the presence of activated macrophages. The responsive nanomaterials developed in this article have promising potential as drug carriers in applications where ROS-triggered delivery of cargo is required such as in inflammatory conditions. Graphical abstract: Image 1 Highlights: Two novel thioether-based diblock copolymers were obtained using post-polymerization modification. Both copolymers self-assemble and form micelles in aqueous solution. ROS-responsive behavior of both copolymers was studied using H2 O2 and in stimulated in vitro inflammatory conditions.